Future Multilateralism
XVII, 319 p.
Keywords: The aim of this volume is to discuss the kinds of multilateralism that would be required to pursue some of the alternative projects of society, namely those which agree with some of the key normative commitments of the MUNS programme: non-violent means for dealing with conflict; social equity; protection of the biosphere; diffusion of power among social groups and societies. The strategies identified here are both 'top-down', ie: relying on conventional international institutions and 'bottom-up', ie: involving a new multilateralism grounded in civil society.